An investigation of risky sexual behaviours, basic HIV knowledge and intention to use condoms among a sample of men who have sex with men in a student community - Brink, Jaco Greeff (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.